Komunistiniai leidiniai jaunimui buržuazijos valdymo metais Lietuvoje (1920–1940.VI.) - Zaveckienė, Žiedūnė (Knygotyra, 1972)
In the period of the bourgeois dictatorship the Young Communist League of Lithuania under the leadership of the Communist Party kept in touch with the working youth mainly through underground press. The YCL of Lithuania took care of publishing and spreading it. At that time not only periodicals and appeals were published but separate books as well In the period of 1920 to June, 1940, were issued more than 60 publications dedicated to the theory and practice of revolutionary movement and the experience of the fight of the working youth in Lithuania. The greatest part of these works appeared in the first years of the dictatorship (1920–1923).The books were published bolh in underground conditions (more than 20 works) and at the Printing-House of the Central Committee of the Communist Party of Lithuania in Smolensk and in some other places. Almost all the publications except those of local organizations were published as printed matter.At the beginning of the underground work in Lithuania in many cases the books in 50 pages and even appeals in several pages were published. The volume and size of these publications corresponded to the demands of conspiracy.